2009
DOI: 10.1038/sj.bjc.6605298
|View full text |Cite
|
Sign up to set email alerts
|

Absence of VHL gene alteration and high VEGF expression are associated with tumour aggressiveness and poor survival of renal-cell carcinoma

Abstract: Background: The von Hippel–Lindau gene ( VHL ) alteration, a common event in sporadic clear-cell renal-cell carcinoma (CCRCC), leads to highly vascularised tumours. Vascular endothelial growth factor (VEGF) is the major factor involved in angiogenesis, but the prognostic significance of both VHL inactivation and VEGF expression remain controversial. The aims of this study were to analyse the relationship between VHL g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 40 publications
7
72
0
Order By: Relevance
“…We report our original data providing evidence that mutant VHL, as found in most sporadic RCC, triggers NK cell activation. Although the correlation between VHL alteration in sporadic RCC and better survival is still controversial (Yao et al, 2002;Banks et al, 2006;Smits et al, 2008), the absence of VHL mutation is associated with tumor aggressiveness and poor survival (Patard et al, 2008(Patard et al, , 2009. Our evidence that NK cells are activated differently by targets that bear or not VHL mutations are consistent with earlier findings that suggest that somatic VHL alteration is associated with better cancer-specific survival among those patients presenting with early stage (pT1 and pT2) clear-cell RCC (Parker et al, 2005).…”
Section: Mutated Vhl Rcc Cells and Nk Cell Activationsupporting
confidence: 88%
“…We report our original data providing evidence that mutant VHL, as found in most sporadic RCC, triggers NK cell activation. Although the correlation between VHL alteration in sporadic RCC and better survival is still controversial (Yao et al, 2002;Banks et al, 2006;Smits et al, 2008), the absence of VHL mutation is associated with tumor aggressiveness and poor survival (Patard et al, 2008(Patard et al, , 2009. Our evidence that NK cells are activated differently by targets that bear or not VHL mutations are consistent with earlier findings that suggest that somatic VHL alteration is associated with better cancer-specific survival among those patients presenting with early stage (pT1 and pT2) clear-cell RCC (Parker et al, 2005).…”
Section: Mutated Vhl Rcc Cells and Nk Cell Activationsupporting
confidence: 88%
“…18 The cell lines were established as stable cell lines after 50 passages. The cells were dissociated and cultured in RPMI 1640 (Invitrogen) supplemented with 10% fetal calf serum (Sigma-Aldrich), 1% penicillin/streptomycin (Sigma-Aldrich) and 10 mM HEPES buffer at 37 C under 5% CO 2 .…”
Section: Cytogenetic Analysesmentioning
confidence: 99%
“…This finding is usually present in ccRCC and makes it difficult to correlate increased expression of this protein with the clinical parameters because most tumors overexpress it. Nevertheless, some studies have found greater expression of the protein in tumors with distant metastasis [20]. One of the proteins activated by increased expression of HIF-1alpha is VEGF, a regulator, among other things, of angiogenesis.…”
Section: Discussionmentioning
confidence: 99%